Visuospatial attentional functioning in amateur boxers - Lesiakowski, P.; Zwierko, T.; Krzepota, J. (Journal of Combat Sports and Martial Arts, 2013)
Attention is an activation state of cerebral cortex that impact the ability to process information. In boxing attention adopted during the execution of a skilled motor action can have a profound effect on performance outcomes. However, boxing is associated with a risk of concussion often leading to cognitive impartments. The aim of this study was to investigate the visuospatial attentional functioning in amateur boxers compared to nonathletes. Material and methods. The research involved 15 elite polish, amateur boxers (10 male and 5 female). All participants are or were the members of National Team in variety of age groups. The control group included 15 nonathletic students of Szczecin. Both groups were homogeneous in terms of age and gender. Special Ability Signal Test included in the Vienna Test System (Schuhfried, Austria) was used to examine long-term selective attention. The test measured the visuospaial differentiation of a relevant signal within irrelevant signals. The main variables calculated were the numbers of correct, omitted and incorrect reactions and the median reaction time as a measure of the speed of the detection process. Results. There was no significant difference between boxers and controls in the variables of numbers of correct responses (p=0.40), reaction time (p=0.07), numbers of omitted reactions (p=0.40), and numbers of incorrect reactions (p=0.87). Conclusions. Amateur boxing does not lead to impairment in visuospatial attentional functioning as well as information processing speed.